The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1751-1097.2008.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in UV Irradiance of Tanning Devices in Norway: 1983–2005

Abstract: Indoor tanning increases skin cancer risk, but the importance of different parts of the UV spectrum is unclear. We assessed irradiance of tanning devices in Norway for the period 1983-2005. Since 1983, all tanning models needed approval before being sold or used. UV Type 3 limits were valid from late 1992 (<0.15 W m(-2) for CIE-weighted, i.e. erythemally weighted, short and long wave irradiances). We analyzed data from 90% of the approved tanning models (n = 446 models) and two large inspection surveys in 1998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 20 publications
(37 reference statements)
2
40
1
Order By: Relevance
“…The UVA and UVB irradiances of approved tanning devices in Sweden were similar to those in Norway, and varied little between 1982/1983 and 1992 (4,29). In this cohort, where women were aged 30 to 49 years in 1991 (i.e., birth cohorts 1942-1961), solarium use before 20 years of age occurred before 1981, use from 20 to 29 years occurred between 1962 and 1991, and use from 30 to 39 years between 1972 and 1991.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The UVA and UVB irradiances of approved tanning devices in Sweden were similar to those in Norway, and varied little between 1982/1983 and 1992 (4,29). In this cohort, where women were aged 30 to 49 years in 1991 (i.e., birth cohorts 1942-1961), solarium use before 20 years of age occurred before 1981, use from 20 to 29 years occurred between 1962 and 1991, and use from 30 to 39 years between 1972 and 1991.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, solarium users were exposed to UVB-rich sunlamps until about 1982/1983 and then UVA-rich fluorescent lamps (4). Mean UVB and UVA irradiances of inspected tanning devices in Norway in 2003 were 1.5 and 3.5 times higher, respectively, than the irradiance of the natural summer sun at noon in Oslo (29). We can assume that these irradiances are similar in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based investigations found that British residents continued to partake in high-risk behaviors and that men from lower socioeconomic groups were at the greatest risk for UV exposure (107). In Norway and Sweden, national campaigns have also been launched in an effort to address rapid rises in melanoma incidence (104,105). Similar to the United Kingdom and the United States, there has been limited and varied success with their preventative measures (104,105).…”
Section: Primary Preventionmentioning
confidence: 99%
“…Nationwide efforts to reduce UV exposure have been attempted with variable success across high-incidence countries like the United States, the United Kingdom, Norway, Australia, and New Zealand (19,102,104,105). In the United States, the indoor tanning industry accrues $3 billion per year in profit (106).…”
Section: Primary Preventionmentioning
confidence: 99%